2021
DOI: 10.1155/2021/6668167
|View full text |Cite
|
Sign up to set email alerts
|

Complement Fixation Test for Specific Antibody Detection against Bovine Brucellosis in Selected Peasant Association of Guto Gida District, East Wollega Zone, Oromia, Ethiopia

Abstract: Brucellosis is one of the major zoonotic diseases yet prevalent in Ethiopia. It is contagious and has harmful effects on free animal movement and export. A cross-sectional study was conducted from November 2016 to April 2017 in the Loko and Uke peasant association of Guto Gida District. The goal of this study is to determine the seroprevalence and associated risk factors of bovine brucellosis. The questionnaire survey was conducted on 200 respondents to collect the livestock owner’s perception of this disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Another cross-sectional study in the Jimma Zone, Oromia Region, has reported an animal and herd level cattle prevalence of 16.4% and 4.3%, respectively [64]. Very recent studies have also recorded a prevalence of 11.9% and 22.5% in Afar National Regional State and East Wollega, Oromia Region, respectively [14,17].…”
Section: Seroprevalence Of Bovine Brucellosismentioning
confidence: 97%
See 1 more Smart Citation
“…Another cross-sectional study in the Jimma Zone, Oromia Region, has reported an animal and herd level cattle prevalence of 16.4% and 4.3%, respectively [64]. Very recent studies have also recorded a prevalence of 11.9% and 22.5% in Afar National Regional State and East Wollega, Oromia Region, respectively [14,17].…”
Section: Seroprevalence Of Bovine Brucellosismentioning
confidence: 97%
“…In the past decade, several bovine brucellosis serological surveys conducted in Ethiopia have shown the endemic and widespread characteristics of the disease. Between 2010 and 2021, seroprevalence studies conducted on bovine brucellosis in Ethiopia have reported prevalence rates ranging from 0.4% to 11.9% at the individual animal level [12][13][14], and 12% to 63.6% at the herd level [15][16][17]. Most previous studies have been performed in central Ethiopia on institutionally owned commercial, large and medium scale dairy farms, situated in Addis Ababa and its surrounding area [18].…”
Section: Introductionmentioning
confidence: 99%